The Effect of Brand Image, Product Quality and Price Toward Purchase Decision (Emprical Study on Consumer Cv.Rown Division in Surakarta) - Susanto, Henry (2016)
ABSTRACT The main purpose of this research is to analyze brand image, product quality and price which determines customer decision to buy the product of CV Rown Division Surakarta. The population in this research is the whole customer of CV Rown Division Surakarta. This research is a quantitative research using factor analysis. Samples taken as research object are 100 respondents who have purchased the product on the CV Rown Division Surakarta and data wastaken by questionnaire. Instrument test used validity test and reliability test. The analysis of data using multiple linear regression validated by the data normality test, multicolinearity test, heteroscedasticity test, determination test, F test and t test. As for processing the data were analyzed with SPSS 21.00 for Windows. The result of the research shows positive and significant effects of brand image (X1), Product quality (X2) and price (X3) on Purchase decision (Y) at CV Rown Division Surakarta.